Has Integration Promoted Business Cycle Synchronization in the Enlarged EU? - Nikolaos Antonakakis; Gabriele Tondl (FIW - Research Centre International Economics, 2011)
This paper examines whether European integration, manifesting itself in increased trade and FDI linkages, new specializations and economic policy coordination, contributed to the synchronization of business cycles in the enlarged EU. We estimate the effects on bilateral growth rate correlations in 1995-2008 in a simultaneous equations model which permits to model endogenous relationships and unveil direct and indirect effects. Trade and FDI prove to have a strong impact on synchronization, specifically between incumbent and new EU members. More coordinated fiscal policies and, particularly in EU 15, the alignment of monetary policies promoted synchronization. Nevertheless, flexible exchange rates remained important adjustment instruments for the new member states. Increasing manufacturing specialization is not counteracting synchronization. The achieved EU income convergence, a declared objective of EU policy, supported business cycle synchronization.
Keywords: E30; E52; E62; F15; F42; F44; 330; Business cycles; transmission channel; FDI; trade; monetary union; EU